2021
DOI: 10.3329/brj.v24i2.53447
|View full text |Cite
|
Sign up to set email alerts
|

Doubling Rice Productivity in Bangladesh: A Way to Achieving SDG 2 and Moving Forward

Abstract: Built on deep-rooted political and cultural heritage, ‘rice security’ is the foundation of ‘food security’ in Bangladesh. The country has been in production-surplus of rice in the current decade feeding over 165 million people. This on-going ‘selfsufficiency momentum’ would require to maintain to meet increased demand from growing future population. On developmental side, Bangladesh is placed among the three of the world’s fastest growing economies in the years through to 2050. Rice sector would need to match … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 26 publications
1
41
0
Order By: Relevance
“…Therefore, to ensure the future food demand of overgrowing populations, we have to sustain or increase the Aman rice production in Bangladesh. Though the rice cultivation area of Aman is higher than Aus and Boro, the yield capacity of Aman varieties is lower than the Boro varieties [5]. Climatic conditions i.e., cloudy weather, low uptake capacity of fertilizer, lowest growing degree days and short life duration are the main causes of low rice yield of Aman season.…”
Section: Plos Onementioning
confidence: 96%
See 4 more Smart Citations
“…Therefore, to ensure the future food demand of overgrowing populations, we have to sustain or increase the Aman rice production in Bangladesh. Though the rice cultivation area of Aman is higher than Aus and Boro, the yield capacity of Aman varieties is lower than the Boro varieties [5]. Climatic conditions i.e., cloudy weather, low uptake capacity of fertilizer, lowest growing degree days and short life duration are the main causes of low rice yield of Aman season.…”
Section: Plos Onementioning
confidence: 96%
“…To increase the regional productivity equally, varietal and management interventions is must. Kabir et al, [5] reported that there are five unexplored areas in Bangladesh, where rice cultivation is possible. They mentioned that greater Barishal region, greater Sylhet region, South-west and greater Jashore region, Coastal charland in Barishal and Noakhali, and Chattogram hill tracts have unexplored areas.…”
Section: Plos Onementioning
confidence: 99%
See 3 more Smart Citations